Financial Performance Appraisal of Asante Akim Rural Bank from the Year 2003 To 2007. - Tweneboa-Kodua, Kwadwo (2011)
A long essay submitted to the Department of Accounting and Finance. Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirements for the Degree of Master of Business Administration